Occurrence of naphthalene in honey consumed in Turkey as determined by high-pressure liquid chromatography - (:unkn) unknown (My University, 2007)
This study is the first report on an investigation of the naphthalene concentration in samples of contaminated honey consumed in Turkey. Naphthalene was detected using high-performance liquid chromatography with a diode array detector at 220 nm. In one suspected contaminated specimen, the presence of naphthalene was confirmed by gas chromatography with mass spectrometry (GC-MS) at a concentration of 1.13 microg/kg. The limit of detection was 0.023 microg/g and the limit of quantification was 0.078 microg/g with signal-to-noise ratios of 3 and 10, respectively. A total of 100 samples of commercially available honey obtained from markets (53 samples) and street bazaars (47 samples) were analyzed. Mean naphthalene recovery from honey known to be contaminated with 1 microg/g was 80.4% (SD = 4.84%, n = 7).
Keywords: Humans; Reproducibility of Results; Turkey; Honey; Sensitivity and Specificity; Food Contamination; Chromatography, High Pressure Liquid; Consumer Product Safety; Gas Chromatography-Mass Spectrometry; Naphthalenes